Malignant fibrous histiocytoma in ankle: case report - Miot, Helio Amante [UNESP]; Ferreira, Cesar Augusto Zago [UNESP]; Shwetz, Ana Claudia Athanasio [UNESP]; Miot, Luciane Donida [UNESP]; Haddad, Gabriela Roncada [UNESP] (My University, 2021)
Malignant fibrous histiocytoma (MFH) or undifferentiated pleomorphic sarcoma (UPS) is a sarcoma capable of invading adjacent structures. It is a mesenchymal neoplasia that predominates in men between the sixth and seventh decades of life. It is located mainly in the lower limbs and may affect the head and neck, trunk, and retroperitoneum, presenting a tendency to recurrence and local metastasis. This report aims to present a case of MFH in the ankle of a 49-year-old woman with an adjacent bone invasion, which evolved with transtibial amputation. Clinical, radiological, histopathological, and therapeutic aspects were addressed, highlighting the importance of early diagnosis
Histiocitoma fibroso maligno no tornozelo: relato de caso
Keywords: Amputation; Malignant fibrous histiocytoma; Sarcoma